Identification of Relationship Maintenance in Chinese Muslim Marriages in Film "Bidadari Mencari Sayap” - Silvia Pristianita; Rustono Farady Marta (ULTIMA Comm, 2021)
Culture and reality in society are often described in various ways, one of which is through literary works such as films. The film is one of the media that is often used to convey the implied meaning and message. "Bidadari Mencari Sayap” is one of the films shown on the side streams of the Disney+ platform. "Bidadari Mencari Sayap,” which officially aired on 2 October 2020, portray a very complex wedding story. This film tells the story of a household between a Muslim husband and wife and a Chinese convert. This study will analyse the film using qualitative methods and interpretative paradigms. In addition, the author will use relational maintenance from Laura Stanford and Canary, which consists of ten elements in maintaining relationships, namely positivity, openness, assurance, sharing tasks, social networks, join activities, mediated communication, avoidance, antisocial and humour. The explanation is elaborated with a grand syntagmatic from Christian Metz Semiotics, namely autonomous shot, the parallel syntagm, the bracketing syntagm, the descriptive syntagm, the alternating syntagm, the scene, and the scene episodic sequence, and the ordinary sequence. The research results show that the film "Bidadari Mencari Sayap” applies eight of the ten elements of relational maintenance theories that produce four syntagms and three autonomous shots with various types, namely subjective insert, explanatory insert also displaced diegetic. The differences between the two characters do not become a barrier, and each partner has their respective duties to maintain the relationship that has been built together. Keywords: Christian Metz Semiotics; Relational Maintenance Theory; Film; "Bidadari Mencari Sayap”